The effect of different amounts of bıotin in broilers' ration on growth performance and fatty liver syndrome - Şakir Doğan Tuncer; Reşat Aştı; Behiç Coşkun; Erdoğan. Şeker; Ülker Demirci (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the effect of different amounts of biotin (0, 50, 100 and 150 y^g/kg) added to the broilers' ration on growth performance and fatty liver syndrome. In this study, 1000 day-old Hybro chicks were used. They were distributed into 4 groups, each group containing 250 chicks and the experiment was ended at the 49th day. Mean final weight values in the groups were 1841.13; 1871.78; 1822.88 and 1848.39 g respectively. There were no significant differences among the live weights of the groups (P > 0.05). But the highest final weight was found in the group fed 50 µ/kg biotin. Total feed consumption for all groups were 4.295; 4.326; 4.378 and 4.294 kg respectively. There was no large variation among the groups related to feed consumption. Feed convertion were found to be 2.340; 2.312; 2.405 and 2.324 kg, respectively, during the experiment. According to these results, experimental group I (50 &mikro;g/kg biotin) consumed less feed for 1 kg weight gain than the others. At the end of the experiment, in macroscopic investigation, livers of the groups given 0 and 50 jkg biotin were seen pale in colour and fatty. In microscopic investigation of the livers in the same groups, severe lipid infiltrations were seen in the cytoplasma of paranchymal cells. The livers of second (100 µ/kg biotin) and third (150 µg/kg biotin) groups were macroscopically normal. Any lipid infiltration in the paranchymal cells were not observed. 50 µg /kg biotin improves the growth performance but the same level was not effective in preventing fatty liver syndrome. As a result, the use of the amount of 100 µ,g /kg biotin would be recommended in preventing the formation of fatty liver syndrome in broiler feeding.